Comparison of Volunteer Non-Remunerated Donors and Replacement Donors - Gurung, Numaya; Shakya, Basu; Rai, Ganesh; Shrestha, Deependra (Journal of Nepal Health Research Council, 2023)
Background: There are mainly two types of blood donor in Nepal i.e., Voluntary Non-Remunerated Donor and Replacement Donor. The main aim of this study is to compare between Voluntary Non-Remunerated Donor and Replacement Donor. Methods: This is retrospective and cross-sectional study conducted in the blood transfusion Service, Tribhuvan University Teaching Hospital. The study was conducted on both Voluntary Non-Remunerated Donor and Replacement Donor who came to blood transfusion Service and voluntary blood donation program. All the blood donors donating in blood transfusion Service were considered as the study population.Results: Out of total 25951 donors, there were 15565(60.02%) Voluntary Non-Remunerated Donor and 10386(39.97%) Replacement Donor. On the whole, there were 21938(84.59%) male donors and 3995(15.40%) female donors. The male Replacement Donor was 14273(93.12%) followed by a male Voluntary Non-Remunerated Donor 7582(73.71%). The female Voluntary Non-Remunerated Donor was 2703(67.65 %) followed by female Replacement Donor 1292(32.34 %).Conclusions: This study concludes that the Voluntary Non-Remunerated Donor is quite low, in comparison to Replacement Donor. 100 % Voluntary Non-Remunerated Donor could not be achieved due to lack of awareness about health and voluntary type of blood donation.Keywords: Blood donation; replacement donors; voluntary non-remunerated donors